- 19

- 0

## Main Question or Discussion Point

Tell me what is wrong with this :)

ln (2) = ln( 1 +1 ) and the power series expansion of ln(1+x) for x=1 gives

ln(2) = 1 - 1/2 + 1/3 -1/4 + 1/5 + ......

= (1 + 1/2 + 1/3 + 1/4 + 1/5 + ......... )

- 2 . ( 1/2 + 1/4 + 1/6 + ..............)

= (1 + 1/2 + 1/3 + 1/4 + 1/5 + ......... )

- (1 + 1/2 + 1/3 + ................)

= 0 = ln (1)

=> 2 = 1 ! huh !

ln (2) = ln( 1 +1 ) and the power series expansion of ln(1+x) for x=1 gives

ln(2) = 1 - 1/2 + 1/3 -1/4 + 1/5 + ......

= (1 + 1/2 + 1/3 + 1/4 + 1/5 + ......... )

- 2 . ( 1/2 + 1/4 + 1/6 + ..............)

= (1 + 1/2 + 1/3 + 1/4 + 1/5 + ......... )

- (1 + 1/2 + 1/3 + ................)

= 0 = ln (1)

=> 2 = 1 ! huh !